Women’s perceptions of food safety risks and vendor practices in northern Tanzania: a mixed-methods analysis - Singh, Nishmeet; Marshall, Quinn; Bliznashka, Lilia; Zakayo, Rachel; Mukasa, Lydia; Torres Chavez, Jose Luis; Malindisa, Evangelista; Jeremiah, Kidola; Kinabo, Joyce; Bellows, Alexandra L.; Olney, Deanna K.; Mwambi, Mercy; et al. (International Food Policy Research Institute, 2025)
We know little about how women in Africa perceive and manage food safety risks for fruits and vegetables, and how these perceptions and practices influence their food choices. To investigate this, we employed a sequential mixed-methods analysis using data from 33 villages across the Arusha and Kilimanjaro regions of Northern Tanzania. Quantitative household surveys were conducted with 2,577 women to document their perceptions of food safety risks associated with fresh fruits and vegetables. Additionally, quantitative surveys assessing food safety facilities and practices were conducted in 14 markets and 108 retail outlets. These data informed the creation of food safety scores for women’s risk perceptions and village-level vendor characteristics. We used the scores to analyse their relationship with household-level consumption and expenditure on fruits and vegetables using mixed-effects regression models. Subsequently, ethnographic research involved in-depth exploration with women from three communities to investigate the factors shaping food safety risk perceptions and their connections to household practices and food choices. Our quantitative findings indicated that women’s perceptions of food safety were associated with household-level consumption and expenditure, while vendor safety characteristics were not. The qualitative insights revealed that social relations, community interactions, and trust were pivotal for women in managing food safety risks. Women used these to assess and address food safety risks. Women were also assisted in minimising risk through their roles as producers, sellers, and household managers. Our analysis highlights the importance of understanding consumer perceptions and their socio-cultural contexts in designing interventions that enhance food safety and promote healthier diets.